Optical devices constructed from ferrocene-modified microgels for H2O2 sensing - Zhang, Qiang Matthew; Berg, Darren; Duan, Jiaqi; Mugo, Samuel; Serpe, Michael (My University, 2016)
Ferrocene-modified poly(N-isopropylacrylamide)-based microgels were synthesized, characterized, and used to construct optical devices (etalons). The response of the microgels and etalons to H2O2 was investigated, and we show that both the microgel diameter and the optical properties of the etalons depend on the solution concentration of H2O2 from 0.6 to 35 mM. This behavior is a direct result of the oxidation of ferrocene, which influences the microgel diameter. This was also demonstrated by electrochemical-mediated oxidation/reduction of ferrocene using cyclic voltammetry. We go on to show that these materials could be used to monitor H2O2 that is generated from enzymatic reactions. Specifically, we show that the H2O2 generated from the oxidation of glucose catalyzed by glucose oxidase could be quantified. Finally, the devices can be reused multiple times via a regeneration process. This investigation illustrates the versatility of the etalon system to detect species of broad relevance and how they could potentially be used to quantify products of biological reactions.
Keywords: glucose sensing; H2O2 sensing; microgels; optical devices; responsive polymer